Robust state estimation and unknown inputs reconstruction for a class of nonlinear systems: Multiobjective approach - Delshad, Saleh S.; Johansson, Andreas; Darouach, Mohamed; Gustafsson, Thomas (Automatica (Oxford), 2016)
We consider a novel method to design H∞ observers for a class of uncertain nonlinear systems subject to unknown inputs. First, the main system dynamics are rewritten as an augmented system with state vector including both the state vector of the main system and the unknown inputs. Then, we design a H∞ reduced-order observer to estimate both state variables and unknown inputs simultaneously. Based on a Lyapunov functional, we derive a sufficient condition for existence of the designed observer which requires solving a nonlinear matrix inequality. To facilitate the observer design, the achieved condition is formulated in terms of a set of linear matrix inequalities (LMI). By extending the proposed method to a multiobjective optimization problem, the maximum bound of the uncertainty and the minimum value of the disturbance attenuation level are found. Finally, the proposed observer is illustrated with an example.